Managing Multiculturalism in Islamic Higher Education: A Case Study at UIN Sunan Kalijaga - Sibawaihi (Prodi Manajemen Pendidikan Islam FITK UIN Sunan Kalijaga Yogyakarta, 2020)
Multiculturalism has been a behaviour practiced in higher education in the effort to face and adapt to globalization. To identify how extent does a higher education institution manage multiculturalism, then ideologies adopted in promoting equality among different groups and strategies applied in paying more attention to underrepresented are identified. The study aims at investigating how multiculturalism has been managed at UIN Sunan Kalijaga by highlighting these two aspects. This is a qualitative study using case study methods. Descriptive analysis was used to seek comprehensive multiculturalism-related knowledge at the university. This research concludes that in promoting equality among different groups, the university adopts Islam, Pancasila, and humanism as its ideologies. As for the strategies applied in paying more attention to underrepresented, they are emphasizing professionalism and proportionality in leadership; realizing the university’s strategic position by opening centres for studies on multiculturalism including by pioneering the establishment of a centre for disabilities and redefining the religious texts dealing with marginal groups; and redesigning curriculum by incorporating the values of multiculturalism in lectures and making multiculturalism a course subject.